An investigation on the secondary transfer of organic gunshot residues. Issue 3 (May 2019) - Maitre, Matthieu; Chadwick, Scott; Kirkbride, K. Paul; Gassner, Anne-Laure; Weyermann, Céline; Beavis, Alison; Roux, Claude
Abstract: Gunshot residues (GSR) are an important forensic trace in firearm-related events. Currently, routine GSR analyses focus on the detection and characterisation of the inorganic components (IGSR). The increasing prevalence of heavy metal-free ammunition challenges these current protocols and there is an increasing interest in how the organic components of GSR (OGSR) can provide complementary information. Similar to the situation with IGSR, OGSR compounds originally deposited on the shooter during the firing process may further be transferred onto another individual or surface. Hence, the aim of this study was to provide additional information regarding the risk of a secondary transfer of OGSR. Two scenarios were investigated, the first one related to the arrest process and the possibilities of a secondary transfer arising between a shooter onto a non-shooter (e.g. between a police officer and a person of interest (POI)). The second scenario concerned the transfer of OGSR onto the non-shooter after handling a firearm for few minutes without discharging it. One calibre was chosen, the .40 S&W calibre, used by several Australian State police forces. A secondary transfer was observed in all cases for the two scenarios investigated, for three compounds of interest: ethylcentralite (EC), diphenylamine (DPA), N -nitrosodiphenylamine ( N -nDPA). The firearm handling scenario resulted in a larger secondary transfer to that of the arrest scenario. Overall, the amounts of OGSR detected on the non-shooter were generally lower than that detected on the shooter and controls after the arrest scenario. The results of this study provide complementary knowledge about OGSR, which can be further used to improve the current practice and the interpretation of OGSR evidence. In particular, it highlights that the secondary transfer proposition must be considered during the interpretation of forensic findings, especially when small amounts of OGSR target compounds are detected. Highlights: Two scenarios involving a secondary transfer of OGSR were assessed in an Australian context. The investigated scenarios involved an arrest simulation and handling a firearm without discharging it. The two scenarios resulted in a significant amount of OGSR being transferred onto the non-shooter. The traces detected on the non-shooter were found to be in a lower amount when compared to the control specimens. Recommendations can be drawn. The contact between officers who discharged their firearm and POI should be restricted.